A randomised trial of sheathed versus standard forceps for obtaining uncontaminated biopsy specimens of microbiota from the terminal ileum. Issue 8 (11th February 2011) - Dave, Maneesh; Johnson, Laura A; Walk, Seth T; Young, Vincent B; Stidham, Ryan W; Chaudhary, Meghana N; FunNell, Jessica; Higgins, Peter D R
Abstract : Background: The study of intestinal microbiota has been revolutionised by the use of molecular methods, including terminal restriction fragment length polymorphism (T-RFLP) analysis. Microbiota studies of Crohn's disease patients have examined samples from stool or from the neoterminal ileum with a standard biopsy forceps, which could be contaminated by colonic bacteria when the forceps passes through the colonoscope channel. Objective: To determine whether sheathed biopsy forceps are able to obtain terminal ileal microbiota samples with less colonic bacterial contamination compared with unsheathed (standard) biopsy forceps. Design: Prospective randomised single-centre study. Patients and methods: Four (paired) biopsy specimens were obtained from adjacent locations in the terminal ileum using the sheathed and standard forceps of 27 consecutive subjects undergoing colonoscopy and the microbiota were characterised using T-RFLP. The Bray–Curtis similarity index between samples (sheathed vs unsheathed forceps) was calculated within patients and significant differences were tested for across all patients. Results: There was not a significant difference in the microbial diversity of samples obtained using sheathed versus unsheathed forceps. The difference in microbial diversity between patients was much greater than the variability within patients by proximal versus distal site or by forceps type. Limitations: T-RFLP is based on PCR amplification, so it is not always sensitive to rare bacterial species. Conclusion: Standard unsheathed forceps appear to be sufficient for microbiota sample collection from the terminal ileum.